Strategi Pengembangan Sumber Daya Manusia Untuk Mewujudkan Sekolah Berbasis Kompetensi - Tengku Darmansah; Salniati Nasution; Khalid Samahangga; Nurul Atika Hasibuan (Jurnal Manajemen Kewirausahaan dan Teknologi, 2024)
Human resource (HR) development is a key element in realizing competency-based schools that are able to face the challenges of the globalization era. This study aims to analyze HR development strategies in educational environments with a systematic approach involving teachers, staff, and students. The research methods used are literature review and direct observation at several competency-based schools in Indonesia. The results of the study indicate that effective HR development includes three main aspects: strengthening teacher pedagogical competence, increasing staff managerial capacity, and forming a learning culture in students. The proposed strategies include ongoing training, empowering digital technology, and collaborating with external parties such as the business world and industry. The implementation of this strategy shows an increase in individual and institutional performance, especially in terms of adaptability to curriculum changes, the use of technology in learning, and student learning outcomes. In addition, it was found that visionary leadership support and adequate facilities are the main supporting factors for the success of HR development in competency-based schools. In conclusion, integrated and competency-oriented HR development not only strengthens school competitiveness but also supports the creation of a globally superior generation.